Know Lupus: a strategic public communication campaign for the Lupus Association (Singapore). - Leong, Serena Li Ting. (2008)
(This thesis consists of 2 parts). Chrysalis is a group of four undergraduates working with the Lupus Association (Singapore) on the “Know Lupus” awareness campaign. It is a project undertaken to raise public awareness and understanding of lupus, and to increase the profile of the patient-support group in Singapore. Strategic public communication is required to achieve the above objectives. This report documents in detail the research, planning, execution and evaluation stages of the communication campaign.